Pengembangan Media Pembelajaran Matematika pada Materi Pecahan di Kelas VII SMP Negeri 3 Kota Tambolaka - Bulu, Martina Sumiyati; Making, Samuel Rex Mulyadi; Kerans, Geterudis; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to produce interactive media on fractional blok board, knowing the validity, practicality and effectiveness of students on fraction material and learning media on the fraction block board. The research method used is the Borg and Gall development model (research and information collection, Planning, Development preliminary from of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementasi). The subjects of this research are students in class VII Tambolaka City 3 Public Middle School. Thus, the results of the validity of the material and media in this research can be stated highly valid ininitial field trial classes 97% and 97,916%, main field test class 98% and 100%, and operational field trial classesempiis 99% and 100%. Practicality results in learning media by validators and students in the test class initial field test 97,5% and (highest 77,5% and lowest 52,5%), test class main 100% and (highest 87,5% and lowest 75%), and trial class operational/empirical 100% and (highest 97,5% and lowest 75%). Where, as a results of student effectiveness, the highest score was 100% and the lowest was 52%.